Juridical Review of Gold Investment in E-Commerce Transactions Based on Positive Law - Jhonathan Tanuwijaya (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This study aims to identify positive legal regulations governing gold investment in e-commerce transactions, examine the impact of positive legal regulations on gold investment in e-commerce transactions, and determine legal protection for parties involved in gold investment in e-commerce transactions. transaction. This study found that there are several positive legal regulations governing gold investment in e-commerce transactions, such as Consumer Protection Law No. 8 of 1999 and Bank Indonesia Regulation No. 19/10/PBI/2017 concerning Payment System Service Providers. The impact of these regulations on gold investment in e-commerce transactions is to provide legal protection for all parties involved, including gold investment. The regulation also stipulates the principles of good governance for payment system service providers, such as data security and confidentiality, as well as consumer protection against abuse and fraud. Legal protection for parties involved in investing in gold in e-commerce transactions depends on compliance by business actors with positive legal regulations governing gold investments in e-commerce transactions. Business actors must adhere to good governance practices, ensure data security and confidentiality, and provide consumer protection against abuse and fraud.